Bioinformatic analysis of endometrial miRNA expression profile at day 26–28 of pregnancy in the mare - Agnieszka Sadowska; Tomasz Molcan; Anna Wójtowicz; Karolina Lukasik; Klaudia Pawlina-Tyszko; Artur Gurgul; Graca Ferreira-Dias; Dariusz J. Skarzynski; Anna Szóstek-Mioduchowska (Scientific Reports, 2024)
Abstract The establishment of the fetomaternal interface depends on precisely regulated communication between the conceptus and the uterine environment. Recent evidence suggests that microRNAs (miRNAs) may play an important role in embryo-maternal dialogue. This study aimed to determine the expression profile of endometrial miRNAs during days 26–28 of equine pregnancy. Additionally, the study aimed to predict target genes for differentially expressed miRNAs (DEmiRs) and their potential role in embryo attachment, adhesion, and implantation. Using next-generation sequencing, we identified 81 DEmiRs between equine endometrium during the pre-attachment period of pregnancy (day 26–28) and endometrium during the mid-luteal phase of the estrous cycle (day 10–12). The identified DEmiRs appear to have a significant role in regulating the expression of genes that influence cell fate and properties, as well as endometrial receptivity formation. These miRNAs include eca-miR-21, eca-miR-126-3p, eca-miR-145, eca-miR-451, eca-miR-491-5p, members of the miR-200 family, and the miRNA-17-92 cluster. The target genes predicted for the identified DEmiRs are associated with ion channel activity and sphingolipid metabolism. Furthermore, it was noted that the expression of mucin 1 and leukemia inhibitory factor, genes potentially regulated by the identified DEmiRs, was up-regulated at day 26–28 of pregnancy. This suggests that miRNAs may play a role in regulating specific genes to create a favorable uterine environment that is necessary for proper attachment, adhesion, and implantation of the embryo in mares.